Molecular and morphological identification of Phylloderma stenops Peters, 1865 (Chiroptera, Phyllostomidae) and new records for Colombia (2019)
Based on revisionary work of recently collected material in Colombian museums we confirm the presence of Phylloderma stenops Peters, 1865 in 6 new localities for the country, including the first record of the species in the dry lowlands of the northern Caribbean coast, and the increase by more than 800 m of the elevational range of the species in Colombia. DNA-barcoding confirmed our morphological identification, and supported a paraphyletic composition of the cis-Andean populations. Our records exemplify the little knowledge on the ecogeographic distribution of this species and provide further evidence to consider this as a widespread but rare species. © Martínez-Cerón et al.